The marvelous child in Heraclitus of Ephesus - Kwietniewska, Malgorzat (Revista Archai, 2020)
In the sentence marked DK22 B52, Heraclitus describes a boy playing with small objects (pessoi). The boy has the entire kingdom at his disposal and he himself is identified with the eon. This famous fragment has been interpreted in numerous ways both by classical philologists and philosophers. Its current interpretation is that it is a metaphor for human life. The child, not yet familiar with rules of social life, introduces elements of randomness and careless play into that life. Meanwhile, comparison of Heraclitus’ sentence with the Old Indic tales, lets recognize in the sentence the mythological theme of the act of creation ”“ God creating and governing the world. Such governing means establishing fundamental mathematical rights ”“ the same rights that are applied in astronomical observations and scientific research as a whole. Hypothesis, that the ancient Indo-European culture affected ”“ through India ”“ Heraclitus, lets better understand this philosopher’s thought which harmonically combines elements of science, religion and arts. The India hypothesis also explains the aura of sublimity and holiness found in our tradition. The aura that was present in the late antiquity thinkers who acknowledged Heraclitus’ sentence and passed it to the Western literature.